Development of a hypoxic nanocomposite containing high-Z element as 5-fluorouracil carrier activated self-amplified chemoradiotherapy co-enhancement. Issue 6 (26th June 2019) - Yang, Cui; Peng, Shan; Sun, Yingming; Miao, Hongtao; Lyu, Meng; Ma, Shijing; Luo, Yuan; Xiong, Rui; Xie, Conghua; Quan, Hong
Abstract : The synergetic effect of chemoradiotherapy achievement is encouraging but significantly hampered by the prevalence of hypoxia, leading to drug/radiation resistance in solid tumours. To address the problem and improve the efficiency of cancer therapy, a lamellar-structure multifunctional graphene oxide (GO) drug-delivery system with an average size of 243 nm, co-delivering of metronidazole (MI), 5-fluorouracil (5-FU) and FePt magnetic nanoparticles (MNPs), was successfully designed and synthesized in the study. The integration of hypoxic drug carrier loading radiosensitizers and chemotherapeutic drugs simultaneously, combines the properties of hypoxia-sensitivity and chemoradiotherapy co-enhancement within a single nanoplatform, which is expected to provide new ideas for cancer treatment. Through in vitro tests, the hypoxia-sensitivity and cytotoxicity of intracellular reactive oxygen species (ROS) of the nanocomposites (NCs) were proved. Moreover, the additive effect between MI, 5-FU and FePt MNPs in cytotoxicity and radiation sensitization aspects is disclosed. It performs an enhanced cell proliferation inhibition and makes up a self-amplified radiotherapy enhancement system that improves radiation efficiency and cell radiosensitivity simultaneously. In conclusion, the study recommended a novel and promising multifunctional nanoplatform which performed a self-amplified effect that activated chemoradiotherapy co-enhancement.